Preparation of Microcrystals in Lipidic Cubic Phase for Serial Femtosecond Crystallography - Liu, Wei (2014)
We have recently established a procedure for serial femtosecond crystallography in lipidic cubic phase (LCP-SFX) for protein structure determination at X-ray free electron lasers (XFELs). LCP-SFX uses the gel-like lipidic cubic phase (LCP) as a matrix for growth and delivery of membrane protein microcrystals for crystallographic data collection. LCP is a liquid-crystalline mesophase, composed of lipids and water. It provides a membrane-mimicking environment that stabilizes membrane proteins and supports their crystallization. Here we describe detailed procedures for the preparation and characterization of microcrystals for LCP-SFX applications. The advantages of LCP-SFX over traditional crystallographic methods include the capability of collecting room temperature high-resolution data with minimal effects of radiation damage from sub-10 µm crystals of membrane and soluble proteins that are difficult to crystallize, while eliminating the need for crystal harvesting and cryo-cooling. Compared to SFX methods for microcrystals in solution using liquid injectors, LCP-SFX reduces protein consumption by 2–3 orders of magnitude for data collection at currently available XFELs. The whole procedure typically takes 3–5 days, including the time required for crystals to grow.